On a Question of Modern Approaches in Studying of a Problem of State Regulation of Charity and Patronage in St. Petersburg the 18-19th Centuries - Alexey Petrovich Isaev; Galina Nikolaevna Pitulko (Управленческое консультирование)
In this article we are talking about contemporary approach to the charity phenomen and questions of state cooperation with philanthropic organizations in the Russian empire of the XVIII-XIX centuries. Authors are considering the present theme on the model of Sankt-Petersburg and coming to a conclusion that there are developing the capital departmental institutions.